2019
DOI: 10.3390/md18010005
|View full text |Cite
|
Sign up to set email alerts
|

Marine Pharmacology in 2014–2015: Marine Compounds with Antibacterial, Antidiabetic, Antifungal, Anti-Inflammatory, Antiprotozoal, Antituberculosis, Antiviral, and Anthelmintic Activities; Affecting the Immune and Nervous Systems, and Other Miscellaneous Mechanisms of Action

Abstract: The systematic review of the marine pharmacology literature from 2014 to 2015 was completed in a manner consistent with the 1998–2013 reviews of this series. Research in marine pharmacology during 2014–2015, which was reported by investigators in 43 countries, described novel findings on the preclinical pharmacology of 301 marine compounds. These observations included antibacterial, antifungal, antiprotozoal, antituberculosis, antiviral, and anthelmintic pharmacological activities for 133 marine natural produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 352 publications
(495 reference statements)
0
46
0
1
Order By: Relevance
“…Marine organisms represent a rich source of many antioxidants that are promising for the development of drugs for the prevention and treatment of various chronic and acute human diseases [51]. Thus, thousands of compounds from various marine organisms such as algae, bacteria, fungi, marine invertebrates or sponges have been screened and 21 of them have demonstrated antiviral activities [17]. In 2018, Fedoreyev et al [2] reported that an antioxidant "soup", containing echinochrome A (pigment of sea urchins), ascorbic acid (vitamin C) and α-Tocopherol (vitamin E) possess in vitro antiviral activity against RNA-containing tick-borne encephalitis virus and DNA-containing herpes simplex virus type 1 [2].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Marine organisms represent a rich source of many antioxidants that are promising for the development of drugs for the prevention and treatment of various chronic and acute human diseases [51]. Thus, thousands of compounds from various marine organisms such as algae, bacteria, fungi, marine invertebrates or sponges have been screened and 21 of them have demonstrated antiviral activities [17]. In 2018, Fedoreyev et al [2] reported that an antioxidant "soup", containing echinochrome A (pigment of sea urchins), ascorbic acid (vitamin C) and α-Tocopherol (vitamin E) possess in vitro antiviral activity against RNA-containing tick-borne encephalitis virus and DNA-containing herpes simplex virus type 1 [2].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…It is not surprising, therefore, that marine pharmacology is increasingly growing. Recently, Mayer et al [17] reported that 21 studies were published in 2014/2015, focusing on marine antiviral drugs acting against human enterovirus 71, human cytomegalovirus, human immunodeficiency virus type-1 (HIV-1), human herpes simplex virus (HSV), influenza virus, hepatitis B virus, murine norovirus, respiratory syncytial virus (RSV) or sindbis virus. The mechanism of action of these compounds is known for five of them, although for the others it is still undetermined [17].…”
Section: Introductionmentioning
confidence: 99%
“…The potential marine products are playing a pivotal role in the identification of novel prototypes and also developing drugs using natural products of the marine environment (Vo & Kim, 2010;Wittine et al, 2019). Over twothirds of the planet has been covered by marine species, making them a major source for novel drug-like compounds (Aneiros & Garateix, 2004;Mayer et al, 2019). Further, a possible vaccine target is viral structural proteins, the development of which is desirable and it is foreseen that the first candidates will be advanced to clinical phase I around mid-2020 (Boopathi et al, 2020;Keener, 2020;Khan, Jha et al, 2020;Letko & Munster, 2020;Sarma et al, 2020;Wrapp et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…So far, lots of antiviral agents have been described from marine invertebrates [9,17,113,[143][144][145][146], where the most promising organisms are represented by marine sponges [147]. Despite the numbers of antivirals found from marine invertebrates, only a few of them are on clinical trials or have been approved for drug marketing [148].…”
Section: Marine Invertebratesmentioning
confidence: 99%